A molecular mechanism of symmetry breaking in the early chick embryo. Issue 1 (December 2017) - Arias, Clemente; Herrero, Miguel; Stern, Claudio; Bertocchini, Federica
Abstract The first obvious sign of bilateral symmetry in mammalian and avian embryos is the appearance of the primitive streak in the future posterior region of a radially symmetric disc. The primitive streak marks the midline of the future embryo. The mechanisms responsible for positioning the primitive streak remain largely unknown. Here we combine experimental embryology and mathematical modelling to analyse the role of the TGFβ-related molecules BMP4 and Vg1/GDF1 in positioning the primitive streak.Bmp4 andVg1 are first expressed throughout the embryo, and then become localised to the future anterior and posterior regions of the embryo, where they will, respectively, inhibit or induce formation of the primitive streak. We propose a model based on paracrine signalling to account for the separation of the two domains starting from a homogeneous array of cells, and thus for the topological transformation of a radially symmetric disc to a bilaterally symmetric embryo.